Physical, psychological, and behavioral problems among children and adolescents in countries with different economic statuses during the COVID-19 pandemic: a systematic review and meta-analysis - Peng, Bo; Reeves, Kara K. L.; Lee, Shara W. Y.; Chung, Tina H. Y.; Hui, Heidi W. L.; Leung, Alfred H. L.; Pang, Johnson C. Y. (Frontiers in Pediatrics, 2023)
Introduction The COVID-19 pandemic has impacted children and adolescents’ physical activity (PA), sleeping patterns, and psychological and behavioral health. Yet, little is known about the differences between those in countries with various economic statuses. Methods Articles published from database inception through 16 March 2022 were retrieved using CINAHL Complete, Cochrane Library, EMBASE, Medline, PubMed, and PsycINFO. High-quality studies that reported the number of participants with parameters associated with PA, sleeping patterns, and psychological and behavioral problems in young people aged under 18 years during the pandemic were included. We referenced the Canadian 24-Hour Movement Guidelines for PA and sleep duration to provide the event rate for young people who were not compliant with the guidelines. The event rate of young people who had decreased sleep quality and experienced psychological and behavioral problems were also investigated. A subgroup analysis was conducted to identify the differences in those in countries with diverse economic statuses. Funnel plot analysis and Egger's test were also conducted to identify any risk of publication bias. Result A total of 66 studies with 1,371,168 participants aged between 0 and 18 years, involving 27 countries, were included. During the pandemic, we identified that 41% (95% CI: 39%, 43%; I2 = 96.62) and 43% (95% CI: 34%, 52%; I2 = 99.42) of young people did not meet the PA and sleep duration recommendation guidelines. In addition, 31% (95% CI: 28%, 35%; I2 = 99.66) of young people had decreased their sleep quality. Yet, no significant difference was found across countries with different economic statuses. However, the event rates of participants with psychological and behavioral problems were 32% (95% CI: 28%, 36%; I2 = 99.85) and 19% (95% CI: 14%, 25%; I2 = 99.72), respectively. In addition, the rate of psychological problems was more severe in those who live in lower middle-income countries (p < 0.001), while the rate of behavioral problems was more severe in those who live in high-income countries (p = 0.001). Discussion During the pandemic, the discouragement of PA, poor sleep quality, and high risk of psychological and behavioral problems are concerning. A large number of young people did not comply with the recommendation guidelines. Timely implementation of recovery plans is critical to address the adverse effects on young people. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=309209, identifier CRD42022309209.